(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
The development and active implementation of information technologies in the modern economy required an assessment of the transformation of the consciousness of the digital society. The digital transformation of the economy has changed approaches to the issue of legal capacity, management of corporations and business processes. Traditional management mechanisms lose their competitiveness when used in isolation from dynamically developing digital technologies. The article examines issues related to the digital legal personality of a corporation (online registration of corporations (electronic (digital) residence of corporations), as well as the activities of directly digital (networked or decentralized autonomous organizations) corporations. Three types of digital corporate governance are distinguished: remote management (with the participation of human), smart management (according to algorithms established by humans) and artificial intelligence management (without human participation). Individual tools for digital corporate management are illustrated, displacing traditional forms of management of the human cognitive system